How Does Islamic Organizations Respond to COVID-19 in Indonesia? A Case Study - Rahvy, Aisyah Putri; Ridlo, Ilham Akhsanu (Universitas Udayana, 2021)
Background and purpose: Indonesia has made several regulations to tackle the corona virus disease 2019 (COVID-19) pandemic, including large scale social limitation (Pembatasan Sosial Berskala Besar (PSBB)). This regulation is related to physical distancing in all sectors and activities, including religious activities. But efforts made by government and other organizations are not enough to ensure society that these regulations will not affect their religiosity. To strengthen this policy, majelis ulama Indonesia (MUI) and other Islamic organizations have made fatwa and official statement about how worships, especially those which are done in groups should be conducted during this pandemic. This paper aims to provide report and analysis of Islamic organizations response during pandemic in relation to Islamic worships during COVID-19 pandemic in Indonesia Methods: This is a case study of Islamic organizations response during pandemic. It includes Majelis Ulama Indonesia (MUI), Muhammadiyah, and Nahdlatul Ulama responses (fatwa and official statement) to this issue and public responses as well. COVID-19 case also compared to vaccine hesitancy case, due to similarities of Islamic organization response between them. Results: Some fatwas had been made by MUI as response to Islamic worships performance during pandemic. But still there were cases like Banjarbaru and Solo case, indicating that fatwas could not guarantee the success of COVID-19prevention in religious worships. Conclusion: Religious and community leaders are needed to strengthen government move by helping government promote and educate people about health issues from religious perspectives. Moreover, some kinds of punishment made by government are needed to strengthen fatwas and rulings, as most of these religious opinions do not have legal enforcement.